Realistic view of mediation in penal matters: The reasons for the failure and remedial measures: [Rzeczywisty obraz mediacji w sprawach karnych: Przyczyny klęski i środki zaradcze] (Studia Prawnicze / The Legal Studies, 2021)
The authors are mediators in penal matters, and at the same time they are involved in criminal law and criminology scientifically. From this perspective, they undertook research on the low interest of victim-offender mediation in the practice of Polish justice. They searched for reasons both in imperfect legal solutions and in attitudes of lawyers and parties. They conducted a series of in-depth interviews with practitioners: prosecutors, judges, advocate and mediator with psychological education. They also referred to the results of their previous surveys and conclusions presented by other researchers. On this basis, they formulated several postulates for the legislator. It should be emphasized that they also remain valid outside the Polish legal system. They may also be valuable to mediators, judges and prosecutors, especially those operating in the area of continental criminal law. Autorki są mediatorkami w sprawach karnych i równocześnie naukowo zajmują się prawem karnym i kryminologią. Z tej perspektywy podjęły badania nad niskim zainteresowaniem mediacją w sprawach karnych w praktyce polskiego wymiaru sprawiedliwości. Przyczyn szukały zarówno w niedoskonałych rozwiązaniach prawnych, jak i w postawach prawników i stron postępowania. Przeprowadziły serię pogłębionych wywiadów z praktykami: prokuratorami, sędziami, adwokatem i mediatorem z wykształceniem psychologicznym. Odniosły się również do wyników swoich poprzednich badań i wniosków przedstawionych przez innych badaczy. Na tej podstawie sformułowały kilka postulatów dla ustawodawcy. Należy podkreślić, że zachowują one aktualność również poza polskim systemem prawnym. Mogą być również cenne dla mediatorów, sędziów i prokuratorów, zwłaszcza tych działających w obszarze kontynentalnego prawa karnego. The authors are mediators in penal matters, and at the same time they are involved in criminal law and criminology scientifically. From this perspective, they undertook research on the low interest of victim-offender mediation in the practice of Polish justice. They searched for reasons both in imperfect legal solutions and in attitudes of lawyers and parties. They conducted a series of in-depth interviews with practitioners: prosecutors, judges, advocate and mediator with psychological education. They also referred to the results of their previous surveys and conclusions presented by other researchers. On this basis, they formulated several postulates for the legislator. It should be emphasized that they also remain valid outside the Polish legal system. They may also be valuable to mediators, judges and prosecutors, especially those operating in the area of continental criminal law.